Evaluación de microorganismos (Trichoderma spp y Pseudomona aeruginosa) para la degradación del PET. (2021)
The present research sought to demonstrate the conditions and capacity of microorganisms to achieve the degradation of long polymer chains such as PET, through bibliographic reviews the process to degrade PET on a pilot scale with the respective financial analysis is proposed. The bibliographic reviews were carried out in search engines and sources such as academic Google, Springer Link and Science Direct. This search determined that Pseudomona aeruginosa is a bacterium whose degradation capacity exceeds 14% (w / w), while the degradation capacity of Trichoderma spp.